Role of speckle tracking echocardiography in patients with myocardial infarction - A. V. Kobets; M. P. Kopytsia; N. V. Tytarenko; Yu. V. Rodionova (Zaporozhye State Medical University, 2021)
All over the world cardiovascular diseases are one of the main reason of morbidity and mortality in the structure of non-communicable diseases, and myocardial infarction has a leading role. Markers of modern advanced ultrasound techniques, speckle tracking echocardiography, play significant role in the detection and assessment of cardiovascular disease. Deviation of them can detect myocardial ischemia, hypertrophy, dystrophy and infiltration, severe systemic diseases, cardiotoxicity of the drugs, etc. This technology significantly improves diagnostic capabilities of transthoracic echocardiography, it allows to assess myocardial function in all three planes (longitudinal, circumferential and radial), in which myocardium moves during cardiac cycle. Speckle tracking echocardiography can determine the volume of myocardial damage, differentiate subendocardial and transmural myocardial infarction, identify viable and fibrous areas of the myocardium, that is confirmed by the results of magnetic resonance imaging. Besides, this method helps to detect and assess mechanical dyssynchrony and also predict the risk of pathological left ventricular remodeling and life-threatening adverse cardiovascular events (arrhythmias, increasing of heart failure, recurrent myocardial infarction, stroke, death, etc.), that is important for patients with acute myocardial infarction to identify high-risk patients. The most studied markers of this technique are longitudinal, circumferential and radial strain, mechanical dispersion and postsystolic shortening. Markers of this ultrasound technique significantly complete other markers of transthoracic echocardiography, such as left ventricular ejection fraction, to assess risk stratification of cardiovascular complications. The value of speckle-tracking echocardiography markers has been demonstrated alone or in combination with other markers.